2020
DOI: 10.20944/preprints202003.0103.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MERS-CoV and SARS-CoV Infections in Animals: A Systematic Review and Meta-Analysis of Prevalence Studies

Abstract: Introduction: Coronaviruses are zoonotic viruses that include human epidemic pathogens such as the Middle East Respiratory Syndrome virus (MERS-CoV), and the Severe Acute Respiratory Syndrome virus (SARS-CoV), among others (e.g., COVID-19, the recently emerging coronavirus disease). The role of animals as potential reservoirs for such pathogens remains an unanswered question. No systematic reviews have been published on this topic to date. Methods: We performed a systematic literature review with meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Usual human coronaviruses, containing alpha and beta coronaviruses, commonly create mild to moderate upper respiratory tract infections (URTI) similar to the common cold [ 47 , 52 , 53 ]. Meanwhile, the novel coronavirus (SARS-CoV-2) causes severe respiratory illness (lungs and upper respiratory tract) and even death in some patients ( Figure 2 ) [ 15 , 16 , 17 , 20 , 27 , 47 , 54 ]. It should be noted that SARS-CoV-2 belongs to beta-CoVs, and its size is between 60 and 140 nm [ 55 ] and approximately 120 nm in diameter [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Usual human coronaviruses, containing alpha and beta coronaviruses, commonly create mild to moderate upper respiratory tract infections (URTI) similar to the common cold [ 47 , 52 , 53 ]. Meanwhile, the novel coronavirus (SARS-CoV-2) causes severe respiratory illness (lungs and upper respiratory tract) and even death in some patients ( Figure 2 ) [ 15 , 16 , 17 , 20 , 27 , 47 , 54 ]. It should be noted that SARS-CoV-2 belongs to beta-CoVs, and its size is between 60 and 140 nm [ 55 ] and approximately 120 nm in diameter [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that SARS-CoV-2 belongs to beta-CoVs, and its size is between 60 and 140 nm [ 55 ] and approximately 120 nm in diameter [ 56 ]. Moreover, some studies reported that SARS-CoV-2 has a zoonotic origin [ 15 , 16 , 17 , 20 , 27 , 47 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the COVID-19 outbreak has been declared a global public health emergency of international concern by the World Health Organization (WHO) [13][14][15]. The original source and the way of transmission to humans is the subject of current studies [6,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases such as Chikungunya ( 11 16 ), Zika ( 17 24 ), Yellow Fever ( 25 28 ), Dengue ( 29 33 ), Oropouche, Madre de Dios virus, Iquitos virus ( 34 , 35 ), Mayaro Fever ( 36 , 37 ), Ebola ( 38 42 ), Nipah virus, arenaviruses such as Lassa ( 43 ), Machupo ( 44 , 45 ), Chapare ( 45 , 46 ), Junin ( 47 ), zoonotic Malaria ( 48 ), Severe Fever with Thrombocytopenia Syndrome ( 49 ), Plague ( 50 ), Crimean-Congo Hemorrhagic Fever, Acute Orally Transmitted Chagas Disease ( 51 54 ), Visceral and Diffuse Cutaneous Leishmaniasis ( 55 , 56 ), Toxoplasmosis ( 57 59 ), Tick-Borne Diseases ( 60 , 61 ), Rift Valley Fever, Tuberculosis ( 62 ), Leprosy ( 63 67 ), Avian Influenza ( 68 – 70 ), Orthohantavirus ( 71 – 75 ), and Toxocariasis ( 76 , 77 ) have posed a significant impact to human health. Furthermore, zoonotic epidemics and pandemic coronaviruses, such as the Severe Acute Respiratory Syndrome (SARS), the Middle East Respiratory Syndrome (MERS) ( 78 82 ), and the ongoing SARS-CoV-2/COVID-19 ( 83 , 84 ) pandemic, have caused a profound economical and social disruption threatening to overwhelm public health systems globally ( 85 ) ( Table 1 ). Most of these pathogens can even cocirculate and coinfect a significant proportion of inhabitants within the same territories ( 11 , 87 94 ).…”
mentioning
confidence: 99%